DETERMINANT OF THE HOUSEHOLD’S EXPENDITURE OF THE RECIPIENTS OF SOCIAL ASSIATANCE PROGRAM IN BANDAR LAMPUNG CITY - Ica Rizki Aneftasari; Bustanul Arifin; Muhammad Irfan Effendi (Agricultural Socio-Economics Journal, 2022)
Poverty is a major concern and a serious problem faced by the entire world population, including Indonesia. One of the programs implemented by the Indonesian government is the Social Assistance Program (PKH). This program is in the form of providing social assistance and protection to the recipients of social assistance program. This study aims to analyze the factors that influence household expenditure on the recipients of social assistance program. This research was conducted in Rajabasa and Bumiwaras Villages, Rajabasa District, Bandar Lampung City. With respondents as many as 76 the recipients of social assistance program taken using the proportional random sampling method from the total population of the recipients of social assistance program Rajabasa and Bumiwaras Districts. To analyze the determinant is by using Ordinary Least Square method. The results showed that the variables of income, the recipients of social assistance program education and the number of family members influenced household’s expenditure in Bandar Lampung City.